Formation and characterization of oil-in-water emulsions stabilized by polyphenol-polysaccharide complexes: Tannic acid and β-glucan. (September 2019) - Li, Ruyi; Peng, Shengfeng; Zhang, Ruojie; Dai, Taotao; Fu, Guiming; Wan, Yin; Liu, Chengmei; McClements, David Julian
Abstract: Oil-in-water emulsions were prepared that were stabilized by a polyphenol (tannic acid, TA) and/or a polysaccharide (β-glucan, BG). The influence of TA concentration and solution pH on the physical stability and microstructure of the emulsions was investigated. Emulsions formed using only BG (1%) contained large droplets that were unstable to flocculation and coalescence. The stability of the emulsions (pH 5) could be enhanced by optimizing the ratio of TA-to-BG used to form them, i.e., TA/BG = 0.4 or 0.5. This effect was attributed to a combination of increased steric hindrance and reduced hydrogen bonding of TA to BG. Transmission electron microscopy (TEM) indicated that increasing the level of TA present increased the compactness and thickness of the TA-BG interfacial layers formed around the oil droplets. Furthermore, the stability of the emulsions to droplet flocculation and coalescence depended on the TA/BG ratio and solution pH. The impact of environmental conditions on emulsion stability was also investigated. Emulsions stabilized by TA-BG complexes (TA/BG = 0.5) remained stable from pH 5 to 9 at ambient temperature and at temperatures ≤60 °C at pH 5, but were highly unstable to salt addition at pH 5. Our results may increase the breadth of applications of β-glucan as a functional ingredient in foods. Graphical abstract: Unlabelled Image Highlights: Complexation of tannic acid (TA) with β-glucan (BG) improved emulsifying properties. O/W emulsions stabilized by TA-BG complexes were successfully prepared. TA addition increased both the compactness and thickness of the interfacial layers. The stability of the emulsions depended on the TA/BG ratio and solution pH.